Apparent and standardized digestibility in broilers fed flaxseed meal with multi-carbohydrase and phytase at 35 days of age - Araujo, Robert Guaracy Aparecido Cardoso [UNESP]; Gallardo Vela, Connie; Roberto Sartori, José [UNESP]; da Trindade Neto, Messias Alves (Canadian Science Publishing, 2021)
The apparent total tract digestibility (ATTD; trial 1) and the apparent (AID) and standardized (SID) ileal digestibility of the amino acids (AA) (trial 2) in flaxseed meal (FM) were evaluated with the addition of exogenous multi-carbohydrase (MC) and phytase (Phy). A total of 80 28-d-old broilers were allotted in a completely randomized design to receive treatments up to 35 d of age. A 2 × 2 factorial design is used to determine the enzyme effects, on the ATTD of dry matter, nitrogen, calcium, phosphorus and fiber, energy use, and the AID and SID of AA, in five replicate cages. There was synergism between MC and Phy on the ATTD of nitrogen and energy. The isolated inclusion of MC or Phy increased the ATTD of dry matter, calcium, phosphorus and fiber of FM. The enzyme inclusion on the AID and SID of AA in FM, established by comparing the means, suggested a better response to the addition of MC + Phy. Supplementation with Phy or combination of MC and Phy was a viable alternative to increase the ATTD of nutrients and energy. The combination of MC + Phy resulted in higher apparent and standardized digestibility of AA from FM.
Keywords: Exogenous enzymes; Ileal digestibility; Nutrient balance; Vegetable by-products